THE KEY CHARACTERISTIC FEATURES OF THE NEW GENERATION IN GEORGIA - Sharashenidze, Nino (Verbum, 2015)
The aim of the research was to study the characteristic features of the new generation in Georgia by means of self-evaluation, namely, what key features they identify regarding the new generation. In order to implement the analysis, a questionnaire was compiled and a survey was carried out among youngsters born in the years between 1980 and 1990. The argumentation of the answers and their analysis explained the basis for the origin and development of these features, which were grouped into categories. For each category, certain sub-categories were outlined. The survey has proved that the existing situation – globalization, development of technology, etc. – influences the new generation and leads to the development of specific features. It can be concluded that the new generation greatly differs from the previous ones. Representatives of the new generation are well familiar with modern technologies, they communicate more easily. Besides, they are more critical and try to re-evaluate outdated traditions. They aspire to independence and new ideas, although all the above-mentioned leads to a certain degree of stress. Thus, the characteristic features of the new generation in Georgia are as follows: addiction to digital technologies, facilitated communication, aspiration to independence, openness to novelty and re-evaluation of traditions, tenacity, freedom of expression, acceptance, superficiality, and stress. These characteristic features reflect not only the peculiarities of the new generation, their aspirations and inclinations, but also current processes in the country and the impact of these processes on the mentality of the community. All the above-mentioned should be taken into account in all fields of life, especially in the system of education.
Keywords: new generation; characteristic features of the new generation; Georgia